The Role of Counselling in English Language Teaching - Britto, M. John (Journal of English Language and Literature (ISSN: 2368-2132), 2014)
Counselling plays a significant role in bringing out a remarkable change in an individual’s personal and professional life. It has entered a number of domains including education. As human problems are mushrooming day by day in this hi-tech world, there is a dire need for finding solutions to those problems. It is counselling that comes to one’s aid to solve one’s problems that are psychological and personal. In English language teaching and learning too, there are multiple problems encountered by teachers and students as well. This paper discusses how counselling is indispensable to English Language Teaching (ELT) for finding solutions to problems faced by English language learners. Exploring the relevance of counselling to ELT, it also seeks to highlight the benefits of integrating it with ELT. It brings out the need for introspection of English language teachers to provide counselling to students. It enumerates various counselling skills, and presents an account of problem-solving method in ELT and eight approaches to counselling.